Sustainable development drivers : the role of leadership in government, business and NGO performance - Zoeteman, Kees (Cheltenham Edward Elgar Publishing Ltd., 2012)
Summary: "Sustainable development cannot be prescribed - rather, it results from conscious personal choices in government, business and NGOs. This thought-provoking book explores both the origins and future of the global sustainable development movement, and provides an original overview of the driving forces of sustainable development, including market forces and past and future trends."
Part I : The Core of sustainable development --
1. Sustainable development: taking responsibility for the whole / Kees Zoeteman --
2. A Short history of sustainable development / Kees Zoeteman and Jaco Tavenier --
3. The Mission reflected in the sustainable development concept: uplifting society / Kees Zoeteman and Hans Mommaas --
4. Can sustainable development be measured? / Kees Zoeteman --
part II : Leadership and individual development --
5. Leadership and sustainability attitudes in personal life / Kees Zoeteman --
6. Individual and organizational development phases towards sustainability / Margarete van den Brink --
Part III : Nations, businesses and markets --
7. Ranking of nations / Kees Zoeteman --
8. Drivers of corporate social responsibility / Johan Graafland and Hugo Smid --
9. Understanding differences in business sectors / Kees Zoeteman -
10. Sustainability attitudes in local area development in the netherlands / Jules Hinssen --
Part IV : NGOs and sustainabel development --
11. NGOs and sustainability attitudes wouter / Kersten, Elena Akadanova and Kees Zoeteman --
12. The Sustainability movement / paul van seters --
13. The Case of the center for human emergence netherlands / Lisette Schuitemaker, Peter Merry and Anne-Marie Voorhoeve --
Part V : Past and future developments --
14. Building consensus for sustainable development / Larry Susskind and Mattijs van Maasakkers --
15. Trends, crises and sustainability / Kees Zoeteman --
16. The Conflict of our time / Otto Scharmer --
Summary from Edward Elgar online
Includes bibliographical references and index.
Keywords: Economic development; SUSTAINABLE DEVELOPMENT; BUSINESS; GOVERNMENT POLICY; POLITICAL ASPECTS; LEADERSHIP; GOVERNMENT